2015
DOI: 10.6004/jnccn.2015.0057
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Recovery and Increased Severity of Paclitaxel-Induced Peripheral Neuropathy in Patients With Diabetes

Abstract: Significantly more dose delays and reductions because of PIPN occurred in patients with DM. Preexisting DM associates with long-lasting significant PIPN in patients treated with wP. Benefits and risks of long-term significant PIPN should be carefully balanced in patients with DM before starting wP chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 0 publications
1
41
0
Order By: Relevance
“…De la Morena et al found similar findings in patients with breast cancer treated with paclitaxel every week. They demonstrated that preexisting diabetes was associated with long-lasting significant neuropathy [20]. As well as with Taxol, several authors have described that diabetic patients are more vulnerable to develop OXLIN.…”
Section: Discussionmentioning
confidence: 99%
“…De la Morena et al found similar findings in patients with breast cancer treated with paclitaxel every week. They demonstrated that preexisting diabetes was associated with long-lasting significant neuropathy [20]. As well as with Taxol, several authors have described that diabetic patients are more vulnerable to develop OXLIN.…”
Section: Discussionmentioning
confidence: 99%
“…In one case-control study of breast cancer patients treated with weekly paclitaxel, diabetes mellitus (DM) was the only independent factor found to predict for delayed recovery. After 2 years, 68.7% of patients with DM (vs 29.2% of women without DM) still experienced CIPN, which was functionally significant (grade 2-3) in 18.2% [18]. …”
Section: Clinical Features Of Cipn Associated With Taxanes and Plmentioning
confidence: 99%
“…5 Taxane-induced peripheral neuropathy (TIPN) usually appears during the 4 to 6 first weeks of treatment 6 with a frequency estimated at 14% with docetaxel and 60% with paclitaxel. 7 Age, 8 body mass index (BMI), 9 taxane type, 10 diabetes, 11 cardiovascular risk factors 10 are described as risk factors.…”
mentioning
confidence: 99%